Abundancia y riqueza de hongos micorrizógenos arbusculares en cafetales del Soconusco, Chiapas, México - Bertolini, Vincenzo (Universidad de Costa Rica, 2018)
In the Mexican economy, particularly in the Soconusco region of Chiapas, the cultivation of coffee generates significant inputs; however, coffee plants are susceptible to pests and diseases, so it is necessary to reinforce its production through sustainable management. In this study, we searched for the native arbuscular mycorrhizal fungi (AMF) that could be used as biofertilizers in coffee cultivation. We collected 21 soil samples coming from seven coffee plantations (Coffea canephora) in the Soconusco region Chiapas, Mexico in November 2015. We isolated the spores of AMF by the wet sieving and decanting method to quantify their abundance, richness and composition of morphospecies, as well as their relationships with soil properties. A total of 20 morphospecies and five new records of AMF were obtained, and the most frequent genera were Acaulospora and Glomus. The Toluca and Victoria sites had higher morphospecies richness (17 spp. c/u) than San Agustín, November 20 and San Luis Nexapa (4-7 spp. c/u); while Providencia and Platanar sites recorded an intermediate richness and the highest values of spore abundance. The dissimilarity of Victoria and Toluca in its composition of AMF, respect to the other sites, was explained by the low concentration of PO4-3 in the soil. P availability, linked to soil acidity, is the factor that could be regulating the AMF communities in the soil of the rhizosphere of coffee trees at Soconusco. We consider that could have consortia of AMF specific for soil P-levels and acidity of coffee sites, i.e. Acaulospora and Glomus consortia, which are common into the environmental conditions of coffee plantations in Mexico. Anyway, we need to examin deeply these strains to evaluate their compatibility and functionality before proposing them as native biofertilizers that promote the development and yield of coffee plantations in this tropical region of Mexico.